Recovery and decision-making involvement in people with severe mental illness from six countries: a prospective observational study - Loos, Sabine; Clarke, Eleanor; Jordan, Harriet; Puschner, Bernd; Fiorillo, Andrea; Luciano, Mario; Ivánka, Tibor; Magyar, Erzsébet; Krogsgaard-Bording, Malene; Østermark-Sørensen, Helle; Rössler, Wulf; Kawohl, Wolfram; et al. (BioMed Central, 2017)
Background: Clinical decision-making is the vehicle of health care provision, and level of involvement predicts implementation and satisfaction. The aim of this study was to investigate the impact of decision-making experience on recovery. Methods: Data derived from an observational cohort study “Clinical decision making and outcome in routine care for people with severe mental illness” (CEDAR). Adults (aged 18–60) meeting standardised criteria for severe mental illness were recruited from caseloads of outpatient and community mental health services in six European countries. After consenting, they were assessed using standardised measures of decision-making, clinical outcome and stage of recovery at baseline and 1 year later. Latent class analysis was used to identify course of recovery, and proportional odds models to investigate predictors of recovery stage and change. Results: Participants (n = 581) clustered into three stages of recovery at baseline: Moratorium (N = 115; 19.8%), Awareness/Preparation (N = 145; 25.0%) and Rebuilding/Growth (N = 321; 55.2%). Higher stage was cross-sectionally associated with being male, married, living alone or with parents, and having better patient-rated therapeutic alliance and fewer symptoms. The model accounted for 40% of the variance in stage of recovery. An increased chance of worse outcome (change over 1 year to lower stage of recovery) was found for patients with active involvement compared with either shared (OR = 1.84, 95% CI 1.15–2.94) or passive (OR = 1.71, 95% CI = 1.00–2.95) involvement. Overall, both process (therapeutic relationship) and outcome (symptomatology) are cross-sectionally associated with stage of recovery. Conclusions: Patient-rated decision-making involvement and change in stage of recovery are associated. Joint consideration of decision practise within the recovery process between patient and clinician is supposed to be a useful strategy to improve clinical practice (ISRCTN registry: ISRCTN75841675. Retrospectively registered 15 September 2010).